Exploring the experiences of stroke survivors, informal caregivers and healthcare providers in Sierra Leone: a qualitative study protocol - Christopher McKevitt; Anthony Rudd; Andrew J M Leather; Peter Langhorne; Catherine Sackley; Andrew Leather; Jessica O'Hara; Daniel Youkee; Charles Wolfe; Martin Prince; Divya Parmar; Melvina Thompson; et al. (BMJ Open)
Introduction Stroke is now the second leading cause of adult death in Sub-Saharan Africa. Developed in dialogue with stroke survivors and caregivers in Sierra Leone, this will be the first study to explore the experience of stroke as well as the perceptions of the barriers and facilitators to accessing stroke care among stroke survivors, informal caregivers and healthcare providers. Findings will inform future stroke research and care in Sierra Leone.Methods and analysis A cross-sectional qualitative study employing semistructured interviews that will be audiorecorded, translated, transcribed and coded.Setting Freetown, Sierra Leone.Participants Interviews with a purposive sample of stroke survivors, informal caregivers and healthcare providers.Analysis Interviews will be coded by two authors and inductively analysed using thematic analysis.Ethics and dissemination This study has received ethical approval from the Sierra Leone Ethics and Scientific Review Committee (8 December 2020) and the KCL Biomedical & Health Sciences, Dentistry, Medicine and Natural & Mathematical Sciences Research Ethics Subcommittee (reference: HR-20/21-21050). The findings of the study and learning in terms of the process of coproduction and involvement of stroke survivors will be disseminated via peer-reviewed publications, conferences, media and lay reports.